2021
DOI: 10.1002/admi.202100717
|View full text |Cite
|
Sign up to set email alerts
|

Dosage‐Dependent Antimicrobial Activity of DNA‐Histone Microwebs Against Staphylococcus Aureus

Abstract: Biofilms are surface-bound microbe assemblies encased in an extracellular matrix including extracellular DNA (eDNA), proteins, and polysaccharides, which allow bacteria to resist host immune clearing mechanisms. [1] One critical biofilm component is eDNA, which helps maintain biofilm structural integrity, [2] as well as counter host antimicrobial peptides [3] and antibiotic treatments. [4] Although eDNA can engage positively with pathogens, it is known to have an important role in the innate immune response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In summary, a material synthesis approach is introduced to dissect the antimicrobial activity of NETs. While we have previously reported on the synthesis of minimal NET-mimetic mesh-like materials composed of DNA and histones, this report further incorporates other crucial NET proteins such as NE and MPO as well as tissue environment factors that affect NET function, such as AAT, into the functional biomaterial modeling of NETs ( 9 , 12 , 53 , 54 ). Placing our focus on antibacterial activity against PAO1, we identified histone, a critical protein in epigenetics often overlooked in antibacterial research, as the most potent antimicrobial among the major NET proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a material synthesis approach is introduced to dissect the antimicrobial activity of NETs. While we have previously reported on the synthesis of minimal NET-mimetic mesh-like materials composed of DNA and histones, this report further incorporates other crucial NET proteins such as NE and MPO as well as tissue environment factors that affect NET function, such as AAT, into the functional biomaterial modeling of NETs ( 9 , 12 , 53 , 54 ). Placing our focus on antibacterial activity against PAO1, we identified histone, a critical protein in epigenetics often overlooked in antibacterial research, as the most potent antimicrobial among the major NET proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these NET proteins are bactericidal at minimum inhibitory concentrations (MICs) for specific bacteria but are present at sub-MIC levels in NETs ( 8 ). In addition, NETs are continuously degraded by enzymes and phagocytes in the physiological environment, making the quantification of NET proteins and elucidation of their contributions a challenging task ( 9 ). Although specific NET proteins have been isolated for study, their antimicrobial activity may deviate from that when incorporated in NETs.…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously described a minimal NET-mimetic microweb, comprised of DNA and histones, for their ability to mimic aspects of the bacteria-suppressive features of NETs [ 10 , 11 ]. We have also described a surface-attached NET-mimetic biomaterial we call DHMs, which have a defined mesoscale structure also comprised of DNA and histones, for their NET-mimetic, immune-cell-activating features [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA–histone mesostructures (DHMs) [ 9 ] and microwebs [ 10 , 11 ] resemble aspects of the chromatin backbone structure of NETs. For example, we previously reported that deoxyribonuclease I (DNase I) degrades both DHMs [ 9 ] and microwebs [ 10 ] in a manner that resembles the nuclease-mediated degradation that NETs undergo.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we used a synthetic NET (sNET) biomaterial based on previous work to mimic the chromatin scaffold of endogenous NETs. 26,30,31 This cell-free protocol can be used to generate NET-like biomaterials without the difficulties associated with in vitro generation and isolation of endogenous NETs or co-culture of neutrophils within the HAE model. To understand the impact of NETs on the viscoelastic properties of mucus, we incorporated the sNETs into a synthetic mucus hydrogel as described in our prior work [32][33][34] and mucus produced by HAE cells.…”
Section: Introductionmentioning
confidence: 99%